2020
DOI: 10.3389/fimmu.2020.01681
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Complement in Pregnancy: From Implantation to Parturition and Beyond

Abstract: The complement cascade was identified over 100 years ago, yet investigation of its role in pregnancy remains an area of intense research. Complement inhibitors at the maternal-fetal interface prevent inappropriate complement activation to protect the fetus. However, this versatile proteolytic cascade also favorably influences numerous stages of pregnancy, including implantation, fetal development, and labor. Inappropriate complement activation in pregnancy can have adverse lifelong sequelae for both mother and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 154 publications
(219 reference statements)
2
61
0
Order By: Relevance
“…The activity of the complement system is enhanced systemically during pregnancy, but the activity is inhibited at the placenta for pregnancy maintenance [ 3 ]. Complement regulation is necessary for a successful pregnancy, and some complement components are favorable in the normal fetal growth at the stage of pre-implantation to placentation [ 4 ]. However, during early pregnancy, complement regulation in the spleen is unclear in ewes.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of the complement system is enhanced systemically during pregnancy, but the activity is inhibited at the placenta for pregnancy maintenance [ 3 ]. Complement regulation is necessary for a successful pregnancy, and some complement components are favorable in the normal fetal growth at the stage of pre-implantation to placentation [ 4 ]. However, during early pregnancy, complement regulation in the spleen is unclear in ewes.…”
Section: Introductionmentioning
confidence: 99%
“…Related clinical data had shown that complement activation is at least partially involved in the progression of non-small cell lung cancer [15]. Several recent studies also confirmed that complement plays an active role in regulating T cell immunity [16,17] and natural killer cells are also bound to CFP through NKp46 receptor [18]. CFP is an important positive regulator of alternative pathway (AP) which acts to stabilize C3 and C5 invertase, and is associated with the destruction of bacteria, neutralization of viruses, and cytolysis of certain red blood cells, and as an important component of the complement substitution activation pathway [19].…”
Section: Discussionmentioning
confidence: 90%
“…Unfortunately, findings emerging in different studies are not always easily comparable: complement determinations were performed in different weeks of gestation and it is well known that pregnancy itself exerts an important influence on the complement components synthesis [20][21][22][23]. Heterogeneity refers even to clinical criteria for study inclusion, with some studies enrolling exclusively women with primary APS and others also women with systemic autoimmune rheumatic conditions.…”
Section: Discussionmentioning
confidence: 99%